EMBRYOLOGICAL AND CLINICAL OUTCOMES OF ICSI–MICROTESE IN NON-OBSTRUCTIVE AZOOSPERMIC PATIENTS WITH A HISTORY OF MUMPS ORCHITIS (Tạp chí Y học Cộng đồng, 2026)
Objective: This study aimed to evaluate the effectiveness of micro-TESE combined with ICSI in patients with non-obstructive azoospermia (NOA) who had a history of mumps orchitis, focusing on sperm retrieval rates, embryological development outcomes, and clinical pregnancy results.Materials and Methods: This retrospective study analyzed 293 patients with NOA who underwent micro-TESE, assessing sperm retrieval rates, hormone profiles, and subsequent embryological and clinical outcomes, with a particular focus on those with a history of mumps orchitis.Results: The overall sperm retrieval rate (SRR) among NOA patients was 59.4% (174/293). Remarkably, patients with a history of mumps orchitis (n=51) had a significantly higher SRR of 94.1% (p < 0.05) than those with other etiologies. Additionally, SRR-positive patients exhibited significantly elevated levels of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) (p = 0.022 and p = 0.015), suggesting a possible compensatory response of the hypothalamic–pituitary–testicular axis. Among the 48 ICSI cycles performed in the mumps orchitis group, the fertilization rate was 70.4 ± 22.7 %, the Day 5 blastocyst formation rate reached 60.4%, the β-hCG positivity rate was 82.8%, and the ongoing pregnancy rate was 69.0%.Conclusion: Micro-TESE combined with ICSI proves to be an effective and optimal treatment for NOA patients, especially those with a history of mumps orchitis, achieving high sperm retrieval and promising ongoing pregnancy outcomes. The findings also underscore mumps as a continuing threat to male fertility in Vietnam, reinforcing the importance of early diagnosis and timely medical intervention.